Adolescent Girl-Mother Communication on Sexual and Reproductive Health Issues Among Students in Fiche Town, Oromia, Central Ethiopia - Mulugeta Feyissa; Tadesse Nigussie; Yitagesu Mamo; Temesgen Aferu (SAGE Publishing, 2020)
Background: Adolescents who have communication about sexual and reproductive health (SRH) with their parents are less likely to participate in risky sexual behaviors and to utilize modern contraceptives. However, communication on SRH issues between adolescents and their parents continues to be below the desired goals in low- and middle-income countries. Objective: To assess SRH communication between adolescent girls and their mothers among students in secondary and preparatory schools in Fiche town, Oromia, Central Ethiopia. Method: An institution-based cross-sectional study was conducted from March 27 to March 30, 2017, using a structured self-administered questionnaire. A total of 181 adolescent female students selected from 2 schools in the town participated in the study. Data were collected on sociodemographic characteristics, student-mother communication, and knowledge about and attitudes toward SRH issues. Multivariable logistic regression analysis was performed, and variables with a P value less than .05 were considered statistically significant. Results: A total of 103 (56.9%) of the students had discussed SRH issues with their mothers. The mothers' educational status (ie, primary school and above, adjusted odds ratio [AOR] = 10.01, 95% CI = 3.55-28.19; the student living with friends, AOR = 5.29, 95% CI = 1.09-25.47; the students' knowledge about SRH issues, AOR = 8.57, 95% CI = 3.61-20.35; and students' attitude toward SRH issues, AOR = 2.79, 95% CI = 1.26-6.15) were identified as independent positive predictors of student-mother communication on selected SRH issues. Conclusion: More than half of the study participants had communication on SRH issues with their mothers. SRH communication was positively associated with maternal educational status, the students' living with friends, and the student's knowledge of and attitude toward SRH issues.